Influence of the logistics chain on customer satisfaction in Asian digital platforms 2018-2023: literature review - Javier Huancacuri, Mayra Medaly; Miñano Rua, Alejandra Del Pilar; Oria More, Jose Antonio; Lizardo Balarezo, Juan Fernando; Matallana Farfan, Gonzalo; Napa Alva, Rosario del Pilar (LACCEI, 2025)
Proper supply chain management is relevant to achieving and maintaining high levels of customer satisfaction. This article with a qualitative approach and with PRISMA methodology seeks to analyze the influence of the supply chain on customer satisfaction on Asian digital platforms in China, India and Japan